Impact of Job Pressure on the Performance and Dedication of Employees (International Journal of Food and Nutritional Sciences, 2022)
Stress is a common issue that affects people in practically every career. Companies today undertake in-depth evaluations of stress management issues that impair workers' performance at work, increase worker turnover, and ultimately influence the objectives and goals of an organization. The study examines how job stress affects academic staff members at private institutions in Chandigarh, Mohali, and Patiala regarding commitment and productivity. Field research was undertaken, and there. Chi-square analysis was performed on the data using statistical methods in SPSS (Version 20). The findings indicated that employee performance is impacted by stress at work.